Learning The Qur'an And Iqro' Among The Millennial Generation In The Simpang Tiga District, Pekanbaru City, Riau Province - Erman, Nilam; Meilany, Merry; Winario, Mohd (Journal of Community Sustainability, 2024)
Learning the Al-Qur'an and Iqro' for the millennial generation in Simpang Tiga Subdistrict, Pekanbaru City, Riau Province, is an effort to increase the younger generation's understanding, skills, interest and religious observance of Islamic teachings. This research aims to evaluate the effectiveness of these learning activities in achieving these goals. The research method used is field study with a qualitative approach through observation, interviews and document analysis. The research results show that Al-Qur'an and Iqro' learning activities have succeeded in increasing the knowledge, skills, interests and religious observance of the millennial generation in Simpang Tiga Village. Interactive and interesting learning methods and an active mentoring role are key factors in the success of this activity. Thus, Al-Qur'an and Iqro' learning activities for the millennial generation in Simpang Tiga Subdistrict can be used as a model in increasing the understanding and religious observance of the younger generation in the area.